The effects of test interval on safety instrumented function (SIF) according to Safety Integrity Level (SIL) value on three phase separator application - Biyanto, T.R. (Society of Petroleum Engineers, 2015)
Test interval is an action to verify Safety Integrity Function (SIF) availability. The detection of SIF availability is depends on appropriate test interval value. The test interval value could affect the value of Safety Integrity Level (SIL). This research proposed to demonstrate the effect of the test interval to the obtained value for the specified SIL on SIF. Therefore, SIL value will fit into the architecture of SIF. The case study that used in this paper is three phases separator. The save guards installed in this case are pressure SIF and the relief valve. The result of this research proved that the increasing value of test interval could increase the SIL value. The three phases separator case study with specific hazardous event frequency shown that 0.2 years or 2.4 months is the appropriate value for the test interval. Copyright 2015, Society of Petroleum Engineers.